The Roman Potters’ Kilns of Colchester - Hull, M.R. (1963)
This is an account of the excavation of eight kilns at Colchester, in Essex, England, found in the course of the work of the Colchester Excavation Committee in 1933 and in 1959. Included are descriptions of artefacts such as pottery and buildings, together with an account of the methodology used to unearth these.